Cutaneous infections in transplants patients recipients and HIV positive patients: comparative study and biblyographic review - Cerdeira, Maria del Carmen Rodrigues; Feijóo, Yolanda C. (Brazilian Journal of Sexually Transmitted Diseases, 2000)
We mode a comparative study between two groups of patients. One group with patients who had ben submitted to transplants of different organs, and the other formed by HIV-infected, both with immunity alterations. We carried out an assessment about the frequency of the cutaneous infections, as well as another about the most common germs. We made an exhaustive revision of the existing bibliography referring to these phathologies,